ANALISIS PENGARUH STABILIZER BASF TERHADAP WAKTU IKAT, SLUMP DAN KUAT TEKAN BETON - Eri Setia Romadhon (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2020)
Abstract Buildings were erected using concrete as the main construction material, both buildings, water, transportation facilities. In some cases, concrete mixes require added materials to support their performance. The purpose of adding material is to change one or more of the properties of concrete, when it is fresh or after hardening. The existence of time demands on the progress of project implementation often forces that readymix concreate can provide the best service to consumers or contractors. Likewise with concrete that can show optimal performance at the time required for normal concrete. Therefore we need an added material that can help the process .astered Delvo type stabilizer from BASF is an added material that can help concrete improve performance, which serves to slow down the binding time of the concrete (setting time), for example due to hot weather conditions, or extend the time for compacting, avoiding cold joint. In this research, admixture delvo type stabilizer from basf is used as a substitute for some cement which aims to determine the bonding time, slump value, and concrete compressive strength by using admixture stabilizer type stabilizer, and this study also uses an experimental method with a total of 10 objects cylinder-shaped test. And using a mixture of admixture delvo type stabilizer 0%, and 1%, the quality of the planned concrete is 35 slump 18 ± 2. Concrete compressive strength testing at 14 and 21 days. Test results show that the use of delvo type admixture stabilizer at the bonding time (setting time) is longer than normal concrete, and in compressive strength testing, normal concrete is higher than concrete with admixture delvo stabilizer, whereas at concrete slump value with admixture delvo stabilizer is higher and can last longer until slump testing for 2 hours, while normal concrete thickens faster. Keywords: Basf stabilizer, bonding time, slump, concrete compressive strength